THE DISCLOSURE OF LIFE EXPERIENCE AND ITS EXPRESSION IN CULTURAL STUDIES PERSPECTIVE - Dwi Retnani Srinarwati (Budapest International Research and Critics University, 2018)
One of the key concepts of cultural studies in dealing with